Iron-coupled inactivation of phosphorus in sediments by macrozoobenthos (chironomid larvae) bioturbation: Evidences from high-resolution dynamic measurements. (September 2015) - Chen, Musong; Ding, Shiming; Liu, Ling; Xu, Di; Han, Chao; Zhang, Chaosheng
Abstract: The effects of chironomid larvae bioturbation on the lability of phosphorus (P) in sediments were investigated through sediment incubation for 140 days. High-resolution dialysis (HR-Peeper) and diffusive gradients in thin films (DGT) techniques were applied to obtain soluble and labile P/Fe profiles at a millimeter resolution, respectively. The larvae bioturbation decreased concentrations of soluble/labile P and Fe by up to over half of the control at the sediment depths of influence up to 70 and 90 mm respectively. These effects continued over 116 days and disappeared on the 140th days due to eclosion of chironomid larvae. Labile P was highly correlated with labile Fe, while a weak correlation was observed between soluble P and soluble Fe. It was concluded that Fe(II) oxidation and its enhanced adsorption were the major mechanisms responsible for the decreases of soluble and labile P. Graphical abstract: Highlights: High resolution techniques were employed to study bioturbation effects on P. Larvae bioturbation decreased the concentrations of soluble/labile P and Fe. Bioturbation effects continued over 116 days and disappeared on the 140th days. Labile P was more sensitive than pore water SRP in response to bioturbation. It proved the mechanism of Fe-coupled inactivation of P in bioturbation sediments. Abstract : Chironomid larvae bioturation decreased the lability of P in sediments from Fe(II) oxidation and enhanced adsorption of P.